Influence of raw material properties on waste-based glass foam (Rudarsko-geološko-naftni zbornik, 2023)
Glass foam tablets were prepared by using mixed glass bottles (green, brown, and white), eggshell waste as a foaming agent, Na-bentonite as binder material, and red mud as an additive, respectively. The influence of the amount of red mud and fly ash on the properties (foaming temperature, mechanical strength, specimen density and porosity, thermal conductivity) of the tablets was studied. The foamed tablets contained 2.5 wt % binder material, 0.1 wt % foaming agent, 5 wt % fly ash, and red mud as additives in different ratios (0 – 40 wt %). After homogenization, the ground raw materials were pressed into tablets at 30 MPa using a hydraulic piston press. The products were heat treated at different temperatures with different heating rates. The final product’s properties were measured (specimen density, thermal conductivity, and mechanical strength through falling and abrasion resistance tests). The most convenient results were shown at 5 wt % red mud in this case, the specimen density and thermal conductivity were the lowest, the values were 0.3 g/cm3 and 0.036 W/mK. If 5 wt % of fly ash was added to the mixture the density value stayed the same, the thermal conductivity increased to 0.048 W/mK, but the mechanical strength of the tablets rapidly increased.